From Theory to Practice: EFL Teachers’ Conceptions and Implementation of Critical Reading - Ilyas, Hamzah Puadi; Istaryatiningtias, Istaryatiningtias; Arifin, Syaadiah; Ma’mun, Akhmad Haqiq (Makassar State University, 2024)
Abstract. To date, research on critical reading has seldom been conducted on EFL teachers and their teaching practices. This research, therefore, investigated how EFL teachers conceptualized critical reading and how these conceptions were implemented in their instructional practices. Twenty-nine teachers who taught English at secondary schools in the areas of Jakarta, Bogor, Tangerang, Bekasi, and Sukabumi with teaching experience ranging from three to 11 years participated in this research through interviews or open-response questionnaires. The findings revealed six main concepts of critical reading conveyed by EFL teachers. The concepts identified were analysis, evaluation, inference/conclusion, interpretation, criticism, and questioning. Concerning the application of these concepts in the classroom, the majority of instructional practices observed matched the teachers' conceptualization. Only a few classroom activities did not refer to those concepts. The findings indicate that EFL teachers have a clear understanding of critical reading and the ability to implement critical reading instruction in their teaching practices. It would be beneficial for teachers to expand the variety of critical reading activities they employ. Additionally, further studies on critical reading could be conducted in different areas and at different educational levels to ascertain how other EFL practitioners implement critical reading activities in their classrooms so that EFL teachers can get more insights and references.Keywords: conception of critical reading, teaching practices of critical reading, elements of critical reading, EFL school teachers, qualitative research